STRATEGI DIREKTORAT BEA CUKAI DALAM PENGAMBILAN KEBIJAKAN PADA PERIZINAN LINTAS NEGARA DI INDONESIA - Ningsih, Noor Syafitriani; Rahim, Samsir; Hamrun, Hamrun (Universitas Muhammadiyah Makassar, 2024)
This study aims to find out how the policy-making strategy taken by Customs regarding the circulation of illegal goods that continues to occur in Nunukan Regency. The number of informants in this study were 6 (six) people. By using data collection techniques interviews, observations, documentation, company documents, and literature studies. The results of this study indicate that, policy making is carried out by the Customs and Excise, namely following the regulations that have been set by the local government. This is the main reference for the performance of customs in carrying out their duties so that the smuggling of illegal goods does not continue to occur in border areas, especially in Nunukan Regency. The policy-making strategy carried out by Customs regarding cross-border licensing in border areas, especially Nunukan Regency follows the process stages of 1) Identification of Problems, the initial action taken by customs in making policies is to carry out sea patrols at each entry and exit of goods. 2) Situation analysis and problem formulation, situational analysis of traffic problems by collecting information including types and forms of illegal goods distribution activities. 3) Development and Analysis of Alternatives, development of alternatives and analysis by seeking alternative policies based on program evaluations that have been carried out. 4) Decision Making, decision making on illegal goods by customs officers in accordance with local government regulations.